The Scope of Comparative Public Administration and the Objectives of Comparative Public Administration Studies - Sri Yulianty Mozin; Alexander H. Badjuka; Fatmawati Latif; Fardan Rumampuk; Mohamad Iqshal Botutihe (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines Comparative Public Administration (SPAN) with a focus on the paradigm shift from a classical approach emphasizing bureaucratic structures to a contemporary, multidimensional, adaptive, and applicable paradigm. The study is significant for understanding cross-country administrative practices as a reference for improving bureaucratic effectiveness, transparency, and public policy quality, particularly in the context of Indonesia’s government facing globalization, digitalization, and societal demands. The research aims to map the scope of SPAN, analyze integrative objectives, and evaluate the relevance of international administrative practices. A qualitative approach through literature review was employed, using content analysis of secondary data from journals, scholarly books, and official documents. Findings indicate that modern SPAN enables comprehensive analysis of public administration, strengthens governance capacity, and enhances bureaucratic responsiveness to local and global dynamics. The shift from purely theoretical orientation toward integrating theory, practice, policy, and global innovation confirms SPAN’s relevance for bureaucratic reform.